The Application and Design Research of Chinese Painting Elements in Cultural and Creative Products - 唐彦 (Pacific International Journal, 2023)
Chinese painting is a treasured art form of the Chinese nation, serving as an important cultural medium for disseminating its humanistic spirit. In current times, while Chinese painting continues to explore and inherit traditional painting techniques, it also engages in cross-border integration and innovation with other art forms. It is imperative to fully excavate the expressive mode, elements, and humanistic values of Chinese painting, selecting, analyzing, and refining the most distinctive cultural elements and applying them to the design of creative products. This paper conducts a study on the successes and challenges in the design and development of cultural and creative products based on Chinese painting through multiple case studies, with the goal of guiding it towards a path of combining protection, inheritance, and development, and to create a series of creative design works that convey the aesthetic essence of traditional Chinese painting. This research inspires innovative and practical ideas for integrating traditional culture and contemporary design research, including how Chinese painting can maximize its cultural value and aesthetic characteristics in the design of creative products, as well as the application and design methods of Chinese painting elements in the cultural and creative industry.